2005
DOI: 10.1017/s0033291704002685
|View full text |Cite
|
Sign up to set email alerts
|

Dose–effect relations in time-limited combined psycho-pharmacological treatment for depression

Abstract: Background. A limited number of psychotherapy sessions in combination with medication is preferable to pharmacotherapy only in the treatment of ambulatory patients with major depression. Whether there is a relation between the number of sessions and the efficacy of the treatment is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 28 publications
3
56
0
Order By: Relevance
“…Systematic studies of the ideal dosage of short-term psychotherapy for gaining the optimal outcome are rare, however. The Second Sheffield Psychotherapy Project (SPP2) of Shapiro et al (1995) and the reports of Dekker et al (2005) and Molenaar et al (2011) found no overall difference in the reduction of depressive symptoms between courses of 8 or 16 psychotherapy sessions.…”
Section: Is Interpersonal Counselling (Ipc) Sufficient Treatment For mentioning
confidence: 99%
“…Systematic studies of the ideal dosage of short-term psychotherapy for gaining the optimal outcome are rare, however. The Second Sheffield Psychotherapy Project (SPP2) of Shapiro et al (1995) and the reports of Dekker et al (2005) and Molenaar et al (2011) found no overall difference in the reduction of depressive symptoms between courses of 8 or 16 psychotherapy sessions.…”
Section: Is Interpersonal Counselling (Ipc) Sufficient Treatment For mentioning
confidence: 99%
“…CBT was based on the principles described by Beck (19) and included behavioral activation and cognitive restructuring according to a session-bysession protocol with homework assignments. Short-term psychodynamic supportive psychotherapy (18,(20)(21)(22)(23)(24) was used to represent the psychodynamic intervention. This modality involved an open patient-therapist dialogue that used supportive and insight-facilitating techniques to address the emotional background of the depressive symptoms by discussing current relationships, internalized past relationships, and intrapersonal patterns.…”
Section: Interventionsmentioning
confidence: 99%
“…In the present analyses, we use data from 2 published, randomized controlled trials conducted between 1993 and 1998 [45,46]. The first trial aimed at efficacy and effectiveness of pharmacotherapy versus the combination of pharmacotherapy with Short Psychodynamic Supportive Psychotherapy (SPSP) [47][48][49][50] (16 sessions) [45].…”
Section: Patient Selectionmentioning
confidence: 99%
“…The first trial aimed at efficacy and effectiveness of pharmacotherapy versus the combination of pharmacotherapy with Short Psychodynamic Supportive Psychotherapy (SPSP) [47][48][49][50] (16 sessions) [45]. The second trial investigated efficacy and effectiveness of a combination of pharmacotherapy with 8 versus 16 sessions of SPSP [46]. Pharmacotherapy in both trials consisted of Inclusion criteria for participation in the trials were age between 18 and 60 years, Diagnostic and Statistical Manual of Mental Disorders, Revised Third Editiondefined major depression (with or without dysthymia) assessed in a structured clinical interview, a 17-item HDRS baseline score of at least 14 points, and written informed consent.…”
Section: Patient Selectionmentioning
confidence: 99%